Experimental Validation of Fractionalized Maxwell Fluid Model of MHD Blood Flow through Bifurcated Arteries for Tumor Treatments - Abdulhamid, Mohammed Gazali; Mohammed, Abubakar; Abdullahi, Isah; Usman, Nafisatu (Mikailalsys Journal of Mathematics and Statistics, 2025)
This study provides an experimental validation of a fractionalized Maxwell fluid model to describe magnetohydrodynamic (MHD) blood flow in bifurcated arteries, with targeted applications in tumor therapy. By incorporating fractional calculus, the model captures viscoelastic memory effects that account for key non-Newtonian properties of blood, including shear-thinning behavior, elastic recovery, and time-dependent stress relaxation under combined electromagnetic and thermal influences. The Homotopy Perturbation Method (HPM) was employed to derive approximate analytical solutions for the governing equations, and the model’s predictions were benchmarked against existing theoretical and experimental data. Numerical simulations indicate that the fractional Maxwell model outperforms classical models in predicting velocity profiles, thermal distributions during hyperthermia treatment, and nanoparticle concentration relevant to drug delivery. The model consistently yields lower mean square errors, demonstrating enhanced accuracy and robustness. These results validate the efficacy of fractional-order modeling in hemodynamic simulations and underscore its clinical potential in improving hyperthermia-based cancer therapies and nanoparticle-mediated drug delivery strategies in complex arterial geometries.